Transcriptomics of long‐term, low oxygen storage coupled with ethylene signaling interference suggests neofunctionalization of hypoxia response pathways in apple (Malus domestica) - John A. Hadish; Heidi L. Hargarten; Huiting Zhang; James P. Mattheis; Stephen P. Ficklin; Loren A. Honaas (Plant Direct)
Abstract Research on how plants respond to hypoxia has concentrated on model organisms where tissues can only survive hypoxic conditions for a few hours to a few days. In contrast, hypoxic conditions are used commercially as a method to prolong the shelf life of Malus domestica (apple) fruit for up to a year of storage without substantial changes in fruit quality, not to mention a lack of tissue death. This ability of apples to withstand protracted hypoxic conditions is an interesting adaptation that has had limited molecular investigation despite its economic importance. Here, we investigate the long‐term apple hypoxia response using a time‐course RNA‐seq analysis of several postharvest storage conditions. We use phylogenetics, differential expression, and regulatory networks to identify genes that regulate and are regulated by the hypoxia response. We identify potential neofunctionalization of core‐hypoxia response genes in apples, including novel regulation of group VII ethylene response factor (ERF VII) and plant cysteine oxidase (PCO) family members.